Efficacy of the Therapeutic Game “Trisquel” in the Treatment of Patients With Substance-Related Disorders Randomized Clinical Study - Piñón-Blanco, Adolfo; Vergara-Moragues, Esperanza; Gutiérrez-Martínez, Olga; Fernández-Palleiro, Patricia; Rodrigues, Sonia; Rodrigues-Amorím, Daniela; Lage-López, María Teresa; González-López, Ana; Velasquez, Teresa; Amorim, Mónica; Lloves-Moratinos, Manuel; Viéitez-Fernández, Isabel; et al. (Frontiers in Psychiatry, 2022)
Substance-related disorders have been consistently associated with the presence of alterations in cognitive and executive functions, which are related to daily functioning, justifying the application of neuropsychological rehabilitation programs in treatment. The main objective of this work was to analyze the effect of the intervention program in board game format "Trisquel" on cognitive performance in a sample of patients with substance-related disorders. An experimental design was carried out with a total of 101 people diagnosed with substance-related disorders who were randomly assigned to the experimental group (Trisquel) and the control group. The experimental group performed two weekly structured sessions during three months, while the control group performed therapeutic activities with the same frequency and intensity. Neuropsychological tests were administered before and after the intervention. After the intervention program in the experimental group, statistically significant improvements were found in the subtests of number key, symbol search, arithmetic, direct digits, inverse digits, total digits, letters-numbers in the processing speed index and in the working memory index with WAIS-III, in the phonetic fluency letter P, phonetic fluency letter M and phonetic fluency letter R subtests, and in the word-reading and word-color subtests of the STROOP test. In the control group, with WAIS-III subtests of arithmetic, letters-numbers and in the working memory index. The results of this study suggest that "Trisquel" can be an effective intervention program to induce improvements in processing speed (psychomotor and reading), attentional subprocesses (focused and sustained) and executive functions (updating and inhibition) in people diagnosed with substance-related disorders.